Stabilitation of strawberry puree during processing - I Gede Pasek Mangku; I Nyoman Rudianta (SEAS (Sustainable Environment Agricultural Science), 2018)
During processing of strawberry products like puree were often found of problems such as loss of changed of red colour anthocyanin, formation of brown pigment and loss of vitamin C. The purpose of this research is to determine the best of precise ascorbic acid and sodium acid pyrophosphate (SAPP) concentrations to produced strawberry puree with a good quality. The research was employed by two factors. The first factor is ascorbic acid concentrations, consist of three levels: ascorbic acid 0,5%, 0,75% and 1,0%. The second factors is sodium acid pyrophosphate (SAPP) concentrations, consist of three levels: SAPP 0,04%, 0,07% and 0,1%. The research was designed by factorial randomized block design with two replications. The data were analyzed by variance analyzed when the treatments result gave significantly effect (P